A spin-refrigerated cavity quantum electrodynamic sensor - Wang, Hanfeng; Tiwari, Kunal L.; Jacobs, Kurt; Judy, Michael; Zhang, Xin; Englund, Dirk R.; Trusheim, Matthew E. (Nature communications, 2024)
Quantum sensors based on solid-state defects, in particular nitrogen-vacancy (NV) centers in diamond, enable precise measurement of magnetic fields, temperature, rotation, and electric fields. Cavity quantum electrodynamic (cQED) readout, in which an NV ensemble is hybridized with a microwave mode, can overcome limitations in optical spin detection and has resulted in leading magnetic sensitivities at the pT-level. This approach, however, remains far from the intrinsic spin-projection noise limit due to thermal Johnson-Nyquist noise and spin saturation effects. Here we tackle these challenges by combining recently demonstrated spin refrigeration techniques with comprehensive nonlinear modeling of the cQED sensor operation. We demonstrate that the optically-polarized NV ensemble simultaneously provides magnetic sensitivity and acts as a heat sink for the deleterious thermal microwave noise background, even when actively probed by a microwave field. Optimizing the NV-cQED system, we demonstrate a broadband sensitivity of 576 ± 6 fT/ Hz around 15 kHz in ambient conditions. We then discuss the implications of this approach for the design of future magnetometers, including near-projection-limited devices approaching 3 fT/ Hz sensitivity enabled by spin refrigeration. Coupling to a cavity enhances the readout fidelity of NV center-based quantum sensors, though thermal noise remains a challenge. Here the authors use spin refrigeration and a nonlinear model to demonstrate a highly sensitive quantum magnetometer with NV centers strongly coupled to a microwave resonator.